Modifikasi Unit PemotonMesin Pencacah Serat TKKS Menggunakan Silinder Pemotong Tipe Reel - Junaidi Junaidi; Adriansyah Adriansyah; Elvis Adril (Pusat Penelitian dan pengabdian kepada Masyarakat (P3M) Politeknik Negeri Padang, 2019)
Oil palm empty fruit bunches (OPEFB) are solid waste from the oil palm plantation industry with a fiber content of ± 70%, and can be used as a composite board reinforcement. From the results of previous studies found that the mechanical properties of composite boards of OPEFB fibers between the left, middle and right parts occur very large differences, this situation occurs because the length of the fiber used is not the same between 3-10 cm. The long fibers in addition to the adhesive mixing process are very difficult and long, also resulting in uneven strength of the boards on each side. The purpose of this study is to modify the design of the TKKS fiber chopping machine cutting unit using a reel type cutting cylinder, making the machine cutting unit, and testing the engine performance. From the results of engine design, the engine capacity is ± 85 kg / hour, the engine size is 110 cm x 36.5 cm x 49 cm, the motor power is 2.5 HP with a rotation of 1450 Rpm. The components of the chopper unit consist of the chopper holder measuring 8 cm x l5 cm x 13 cm, placed 3 pieces of planers which are 8 cm x 5 cm x 0.4 cm, the chopper shaft measuring 40 cm long and Ø 3 cm, the holder of the pin measuring Ø 16 cm with a thickness of 0.6 cm. From the results of engine performance testing, it is found that the capacity of the machine with 5 mm filter diameter is 35 kg / hour, diameter of 10 mm 48 kg / hour, diameter 15 mm 55 kg / hour and diameter of 20 mm is 65 kg / hour. The uniformity of the results in the filter hole 5 mm the average fiber length of 15-25 is 80%, the filter hole 10 mm fiber length an average of 30-40 mm by 82%, the filter hole 15 mm fiber length an average of 40-50 mm by 85%, and the filter hole 20 mm in fiber length an average of 50-60 mm by 80%.